PENGARUH MODEL PEMEBELAJARAN TEAM GAMES TOURNAMENT (TGT) TERHADAP PRESTASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN SKI DI MTS. AT-THOLIBIN LAMPUNG UTARA - Riska Rojiatun; Baharudin Baharudin; Era Octafiona (Jurnal Bilqolam Pendidikan Islam, 2025)
This study aims to examine the effects of the Team Games Tournament (TGT) learning model on the learning outcomes of eighth-grade students in the subject of Islamic Cultural History (SKI) at MTs At-Tholbin in North Lampung. The approach used is quantitative with a quasi-experimental research design that includes a pre- and post-test. The study sample consists of two classes: Class VIII A as the experimental group, in which the TGT model was applied, and Class VIII B as the control group, in which conventional teaching took place. An essay test, whose validity and reliability had been verified, was used as the measurement instrument. Data analysis was performed using a t-test for independent samples. The result of the study yielded a significance value of 0.000 < 0.05, indicating a clear and significant difference in learning outcomes between the experimental group and the control group. This proved that the Team Games Tournament (TGT) learning model has a positive influence on students' learning outcomes in the subject of Islamic cultural history.